Controlling cyanobacterial harmful blooms in freshwater ecosystems - Paerl, Hans W. (Microb Biotechnol, 2017)
Cyanobacteria's long evolutionary history has enabled them to adapt to geochemical and climatic changes, and more recent human and climatic modifications of aquatic ecosystems, including nutrient over‐enrichment, hydrologic modifications, and global warming. Harmful (toxic, hypoxia‐generating, food web altering) cyanobacterial bloom (CyanoHAB) genera are controlled by the synergistic effects of nutrient (nitrogen and phosphorus) supplies, light, temperature, water residence/flushing times, and biotic interactions. Accordingly, mitigation strategies are focused on manipulating these dynamic factors. Strategies based on physical, chemical (algaecide) and biological manipulations can be effective in reducing CyanoHABs. However, these strategies should invariably be accompanied by nutrient (both nitrogen and phosphorus in most cases) input reductions to ensure long‐term success and sustainability. While the applicability and feasibility of various controls and management approaches is focused on freshwater ecosystems, they will also be applicable to estuarine and coastal ecosystems. In order to ensure long‐term control of CyanoHABs, these strategies should be adaptive to climatic variability and change, because nutrient‐CyanoHAB thresholds will likely be altered in a climatically more‐extreme world.